2008
DOI: 10.1007/s10029-008-0333-9
|View full text |Cite
|
Sign up to set email alerts
|

Lower gastrointestinal bleeding: an unusual manifestation of inguinal hernia

Abstract: Inguinal hernia is a common condition that usually presents with swelling and mild groin discomfort. Complications include bowel obstruction and strangulation. We report a case of a 50 year-old man who developed lower gastrointestinal bleeding secondary to an indirect inguinal hernia. Colonoscopy showed an ileocecal valve polyp, florid inflammation of cecum and ascending colon and ulcerations of the terminal ileum. Histology showed nonspecific colitis and angiodysplasia of the polyp. Surgical correction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It has been found that an average of 3-6cm circular defect at the neck of the hernial sac is the diameter that allows passage of a standard adult colonoscope and been trapped within [2] . Several cases of incarcerated inguinal hernia that had led to difficulty in colonoscopy have been reported in the literature with different presentations that occurred during and after colonoscopy; some were brief, while others led to bowel ischemia and ulcerations [3] . Incarceration of inguinal hernia within a loop of the bowel has been reported to have occurred even after the completion of colonoscopy [4] , thus expanding the possibility of post-procedural side effects such as intestinal ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that an average of 3-6cm circular defect at the neck of the hernial sac is the diameter that allows passage of a standard adult colonoscope and been trapped within [2] . Several cases of incarcerated inguinal hernia that had led to difficulty in colonoscopy have been reported in the literature with different presentations that occurred during and after colonoscopy; some were brief, while others led to bowel ischemia and ulcerations [3] . Incarceration of inguinal hernia within a loop of the bowel has been reported to have occurred even after the completion of colonoscopy [4] , thus expanding the possibility of post-procedural side effects such as intestinal ischemia.…”
Section: Discussionmentioning
confidence: 99%